Cable Materials for Extreme Environments. - Kell, R. M.; Bennett, Bailey; Stickney, P. B. (1968)
The objective of this program is to develop improved polymeric materials for use in coaxial and multiconductor cables. Emphasis is on improved performance under both arctic and tropical conditions. Tests were carried out to aid in the selection of insulation for compact multiconductor cables. (Author)